ANALISIS KESULITAN BELAJAR SISWA DALAM MATERI PECAHAN KELAS V SD YPK SILO KABILOL - Romima Wakaf; Desti Rahayu; Kartika Tiara (Al-SAMBASY: Jurnal Kajian Pendidikan, 2025)
This study aims to describe the factors that cause fifth-grade elementary school students to experience difficulties in learning fractions. This study was motivated by the difficulties experienced by fifth-grade students at YPK Silo Kabilol Elementary School in learning fractions. The objectives of this study are to describe the factors that cause students' learning difficulties in fractions and the efforts made to overcome these difficulties. This study uses a qualitative approach with data collection through observation, interviews, questionnaires, and documentation. The instruments used in this study include observation sheets, questionnaires for teachers and students, and interview guidelines. Data analysis was conducted using the triangulation method to ensure the validity of the data obtained. The results showed that the factors causing students' learning difficulties in fractions included a lack of understanding of basic fraction concepts, such as distinguishing between numerators and denominators, and understanding fractions as part of a whole. In addition, a lack of motivation to learn, an unfavourable classroom atmosphere, and low support from families also contributed to the difficulties experienced by students. Efforts made by teachers to overcome these difficulties included providing assistance using learning media and holding tutoring activities for students. This study recommends that teachers use more varied and contextual learning methods and increase family support in the student learning process. It is hoped that with these efforts, students' difficulties in learning fractions can be minimised and the learning process can be more effective.